Pharmacokinetic Herb-Drug Interactions involving african traditional medicines - fingerprint analysis and in vitro metabolism studies - Kumar, Saneesh (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.